The Ndalem Wuryaningrat Hall of Pillars in Aesthetic Studies - Wardhana, Sakundria Satya Murti; Santosa, Imam; Wibisono, Andriyanto; Sunarya, Yan Yan (Journal of Ecohumanism, 2024)
The Ndalem Wuryaningrat is a Javanese noble heritage building with Javanese cultural significance designed exclusively for noble descendants. This research aims to show four main pillars in Javanese building known as soko guru. Not only does the soko guru pole serve as a foundation, but it also represents Javanese cultural values. This research method is ethnographic, which examines meaning through direct observation and interviews with sources. The results of this study are the meaning behind the hierarchy of soko guru in The Ndalem Wuryaningrat. Each element's meaning is strongly tied to Javanese cultural notions and reflects its owner. Even though it changed shape throughout the preservation of the Ndalem Wuryaningrat building, the shape of the soko guru pillar at Ndalem Wuryaningrat remains intact and has Javanese cultural significance. This study discovered that the soko guru pole symbolizes Javanese culture and the owner's position through the pole system, shape, and pattern. The conclusion of this research is soko guru pole represents Javanese culture and is associated with the Javanese people's belief in Islam through the soko guru pole features meaningful columns, motifs, and embellishments.